Surveillance load: a burden of search borne by black and brown bodies - Chu, Sarah P. (Critical criminology, 2023)
Racial threat hypothesis contends that growing minority populations produce a threat to social order that results in the weaponization of the criminal justice apparatus. We hypothesize this threat has resulted in the incommensurate surveillance of Black and Brown communities. We define this phenomenon as surveillance load, the disproportionate accumulation or "load" of social control which grows heavier as surveillance technologies and strategies amass. Assessments of these tools are typically conducted in a vacuum without contemplating the collective impact of the larger surveillance infrastructure on Black and Brown communities. We use the application of surveillance technologies in NYC to illustrate surveillance load and argue that unregulated government use of location, biometric, and identity surveillance technologies has exacerbated racial disparities in policing, is amplified by counterterrorism strategies, and outpaced Fourth Amendment jurisprudence. Finally, we propose policy recommendations that create system-level controls over surveillance technologies and engage affected communities.